Photon replacement: A versatile tool for non-Gaussian continuous-variable quantum optics - Bartley, T; Walmsley, I (Optical Society of America, 2014)
Photon replacement is the conditional interference between a single-photon and a multi-photon superposition state, resulting in a range of quantum phenomena. We present results pertaining to quantum state engineering, entanglement distillation, and non-orthogonal state discrimination. © OSA 2014.